The urgency of ijtihad - Ahmed, Moinuddin (New Delhi, India : Kitab Bhavan, 1992)
On the different aspects of theological decision (ijtihad) under Islamic law.
Includes index.
Includes bibliographical references (p. [132]-136).
Keywords: Islamic law -- Interpretation and construction